Obstructing Colonic Mass: A Case of Recurrent Endometrial Cancer - Victor Chedid; Mona Arasoghli; Jana G. Hashash (Case Reports in Gastrointestinal Medicine)
A 71-year-old female with a history of endometrial cancer presented to our hospital with bilateral lower quadrant abdominal pain, which had been worsening over the past two months. The pain was associated with constipation, pencil-thin stools, and a 60 lb weight loss. On physical examination, the patient had suprapubic and left lower quadrant abdominal tenderness. Contrast-enhanced CT scan revealed a 6 cm pelvic mass in the left lower quadrant. It was unclear if this mass was arising from the sigmoid colon or abutting it. A colonoscopy to further investigate the mass was pursued and this revealed a moderate 5 cm long stenosis in the sigmoid colon starting at 15 cm from the anal verge. The stenosis was not ulcerated but had a bluish/purplish hue to it circumferentially. Multiple biopsies were obtained from that area and these revealed architectural changes with mild fibrosis but no malignancy. The mass was further explored with CT-guided fine needle aspiration. The results obtained were positive for cytokeratin-7, CA-125, estrogen receptor protein, and PAX-8 confirming that the mass was endometrial in origin.